Pengabdian Masyarakat Melalui Analisis Dampak Taman Keanekaragaman Hayati PT. Tirta Investama Di Kabupaten Banyuwangi - Kuswanto, Wawan; Tarmudi, Imam; Annas, Muhammad (IAI Darussalam, 2024)
Indonesia is one of the countries with the highest level of biodiversity in the world. However, what is happening is that the amount of forest destruction occurring in Indonesia is still increasing. There needs to be concrete steps to protect Indonesia's nature, one way to overcome forest destruction is the construction and development of biodiversity parks (Kehati). Through the PT. CSR program Tirta Investama in Banyuwangi Regency, since 2020 has been designing a biodiversity park that can be a means of protecting flora and fauna and can have an impact on the environment and humans. This research was carried out to find out and analyze the extent to which biodiversity parks in Banyuwangi are able to have a positive impact. This research uses a qualitative descriptive case study method. Data collection techniques were carried out using observation methods, in-depth interviews, document studies and audio visuals. The data obtained was analyzed in accordance with the theory referred to and described in full. The result is that the Banyuwangi Biodiversity Park, named Raung Kehati Park, is able to have a positive impact on protecting flora and fauna, contributes to carbon reserves, and is able to empower the community, even though the economic aspect has not been felt directly.